Successful cure of daptomycin-non-susceptible, vancomycin-intermediate Staphylococcus aureus prosthetic aortic valve endocarditis directed by synergistic in vitro time-kill study. Issue 4 (3rd April 2019) - Sumon, Zarchi E.; Berenson, Charles S.; Sellick, John A.; Bulman, Zackery P.; Tsuji, Brian T.; Mergenhagen, Kari A.
Abstract: Infectious complications following surgical valve replacements are extremely difficult to treat, often requiring prolonged antimicrobials therapy with or without surgery. Vancomycin-intermediate Staphylococcus aureus is an infrequent pathogen, with an estimated prevalence of less than 0.3%, but presents even greater challenges. We report a case of successful cure of daptomycin-non-susceptible and vancomycin-intermediate Staphylococcus aureus prosthetic valve endocarditis using an eight-week course of combination antimicrobial therapy. Using time-kill study, the combination of daptomycin plus ceftaroline and rifampin resulted in a greater than 4 log reduction of bacterial growth at 24 hours. This antimicrobial combination was used for a total of eight weeks with a successful outcome.